Answer:option C is the correct answer
Explanation:
The given equation is
6x - 2y = 11
Let us make x the subject of the formula. The first step is to add 2y to both the left hand side and the right hand side of the equation. It becomes
6x - 2y + 2y = 11 + 2y
6x = 11 + 2y
Dividing both the left hand side and the right hand side of the equation by 6. It becomes
6x/6 = (11 + 2y)/6
x = (11 + 2y)/6
We would substitute x = (11 + 2y)/6 into (9^3x)/(9^y). It becomes
[9^3(11 + 2y)/6 ] / (9^y)
= [9^(11 + 2y)/2 ] / (9^y)
= [9^(5.5 + y)/] / (9^y)
We would apply the law of indices
a^b/a^c = a^(b - c)
Therefore
[9^(5.5 + y)/] / (9^y) = 9^(5.5 + y - y)
= 9^(5.5)
= 3^2(5.5)
= 3^11